Multipulse Three-Dimensional Alignment of Asymmetric Top Molecules - Ren, Xiaoming; Makhija, Varun; Kumarappan, Vinod (My University, 2014)
We show, by computation and experiment, that a sequence of nonresonant and impulsive laser pulses with different ellipticities can effectively align asymmetric top molecules in three dimensions under field-free conditions. By solving the Schrödinger equation for the evolution of the rotational wave packet, we show that the 3D alignment of 3,5 difluoroiodobenzene molecules improves with each successive pulse. Experimentally, a sequence of three pulses is used to demonstrate these results, which extend the multipulse schemes used for 1D alignment to full 3D control of rotational motion.